2018
DOI: 10.1111/jam.13668
|View full text |Cite
|
Sign up to set email alerts
|

Rumen bacteria at work: bioaugmentation strategies to enhance biogas production from cow manure

Abstract: A close look at the biotic interactions and their associations with abiotic factors might be valuable for evaluating rumen-related bioaugmentation applications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(29 citation statements)
references
References 38 publications
2
21
0
5
Order By: Relevance
“…On the other hand, the role of Oscillospira is still unknown and it is hypothesized that it may be involved in lignocellulose degradation (Kamagata, ). Rickenellaceae, with the genus Alistipes , and Desulfovibrionaceae have also been described in association with the guts of different animals (Koneru et al ., ; Ruengsomwong et al ., ), especially termites (Reid et al ., ; Makonde et al ., ), where they play an important role in the degradation of cellulose polymers (Ozbayram et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, the role of Oscillospira is still unknown and it is hypothesized that it may be involved in lignocellulose degradation (Kamagata, ). Rickenellaceae, with the genus Alistipes , and Desulfovibrionaceae have also been described in association with the guts of different animals (Koneru et al ., ; Ruengsomwong et al ., ), especially termites (Reid et al ., ; Makonde et al ., ), where they play an important role in the degradation of cellulose polymers (Ozbayram et al ., ).…”
Section: Discussionmentioning
confidence: 97%
“…32,33 The CRF was predominated by Bacteroidetes (54%) and Firmicutes (31%) at phylum level, in which Prevotellaceae was the most abundant family. 15…”
Section: Initial Characterization Of Substrates and Inoculamentioning
confidence: 99%
“…13,14 For instance, rumen fluid and/or rumen-derived enrichment cultures were used as co-inoculum in AD and increased the methane generation in a considerable amount. 15,16 High cellulolytic activity of the rumen microorganisms (i.e., bacteria, fungi, and protozoa) have been recently reported to contribute to enhanced substrate degradation and elevated methane production in return. [17][18][19] Inoculum to substrate (I:S) ratio is another significant parameter in the assessment of anaerobic batch digesters and the I:S ratio significantly affects the methane production.…”
mentioning
confidence: 99%
“…showed the percentage of methane (CH4) production at incubated temperature 25C and 39C. This results indicated that the percentage of CH4 production in Hungate tubes incubated at room temperature 25C was similar for the 1 st week up to 8 th week [8]. In contrast, the percentage of CH4 produced in Hungate tubes incubated at room temperature of 39C was increased from a 1 st week up to a 3 rd week, then decreased until the 8 th week.…”
Section: Proportion Of Biogasmentioning
confidence: 93%
“…Therefore, investigation of the viability of anaerobic bacteria consortium of beef cattle feces in a growth media is very important. By growing the rumen bacteria into the growth medium is intended for the bacteria to adapt and allowed the bacteria easily to grow when applying as a starter biogas [6][7][8]. This paper aims to determine the viability of an anaerobic bacterial consortium of beef cattle feces in a liquid medium incubated at temperatures of 25C and 39C to evaluate the potency of this anaerobic bacterial consortium as a starter in the biogas formation.…”
Section: Introductionmentioning
confidence: 99%